'Statistics 102' for multisource-multitarget detection and tracking - Mahler, Ronald (Institute of Electrical and Electronic Engineers, 2013)
This tutorial paper summarizes the motivations, concepts and techniques of finite-set statistics (FISST), a system-level, 'top-down,' direct generalization of ordinary single-sensor, single-target engineering statistics to the realm of multisensor, multitarget detection and tracking. Finite-set statistics provides powerful new conceptual and computational methods for dealing with multisensor-multitarget detection and tracking problems. The paper describes how 'multitarget integro-differential calculus' is used to extend conventional single-sensor, single-target formal Bayesian motion and measurement modeling to general tracking problems. Given such models, the paper describes the Bayes-optimal approach to multisensor-multitarget detection and tracking: the multisensor-multitarget recursive Bayes filter. Finally, it describes how multitarget calculus is used to derive principled statistical approximations of this optimal filter, such as PHD filters, CPHD filters, and multi-Bernoulli filters. © 2007-2012 IEEE.